NUMERICAL PREDICTION OF VERTICAL SHIP MOTIONS AND ADDED RESISTANCE - Cakici, F.; Kahramanoglu, E.; Alkan, A. D. (ROYAL INST NAVAL ARCHITECTS, 2017)
Along with the development of computer technology, the capability of Computational Fluid Dynamics (CFD) to conduct `virtual computer experiments' has increased. CFD tools have become the most important tools for researchers to deal with several complex problems. In this study, the viscous approach called URANS (Unsteady Reynolds Averaged Navier-Stokes) which has a fully non-linear base has been used to solve the vertical ship motions and added resistance problems in head waves. In the solution strategy, the FVM (Finite Volume Method) is used that enables numerical discretization. The ship model DTMB 5512 has been chosen for a series of computational studies at Fn=0.41 representing a high speed case. Firstly, by using CFD tools the TF (Transfer Function) graphs for the coupled heave pitch motions in deep water have been generated and then comparisons have been made with IIHR (Iowa Institute of Hydraulic Research) experimental results and ordinary strip theory outputs. In the latter step, TF graphs of added resistance for deep water have been generated by using CFD and comparisons have been made only with strip theory.
Keywords: REGULAR HEAD WAVES; UNCERTAINTY ASSESSMENT; SIMULATIONS; MODEL; CFD; Engineering